Evaluation of Functional Results and Local Recurrence in Enbloc Resection of Campanacci Grade 3 Giant Cell Tumor of Distal Radius and Wrist Arthrodesis Using Ulnar Translocation Technique: Ulnar Translocation in Giant Cell Tumor - Rashid, Muhammad; Saud, Abdul Munaf; Raza, Tauseef; Napar, Abdul Rasheed; Hussain, Baqir (Pakistan Journal of Health Sciences, 2025)
Reconstruction following en-bloc resection of a distal radius GCTB of Campanacci grade 3 can be difficult. Objective: To examine the outcomes of patients who had ulnar translocation correction and wrist arthrodesis for Campanacci grade 3 distal radius GCTBs. Methods: This retrospective study was comprised of 22 patients. After obtaining informed written consent detailed demographics were recorded. A follow-up clinical evaluation was conducted to determine the functional status and any problems. The MSTS and DASH scores, which measure impairments in the musculoskeletal system, were used to assess the functional outcomes. The MSTS and DASH scores were compared before and after the operation using paired t-tests. At a significance level of P less than 0.05, statistical differences were recorded. Results: The included cases had mean age 30.7±6.28 years. The majority 15 (68.2%) were females and 7 (31.8%) cases were males. Mean follow up was 33.25±9.38 months. Mean length of tumor resection was 8.97±5.79 cm. Before surgery, mean MSTS was 10.84±3.35 and after surgery mean MSTS was 26.01±3.19 p value <0.05. At admission, the mean DASH score was 40.14±14.66 and after surgery decreases to 8.91±12.51 with p value <0.05. Frequency of recurrence rate was 3 (13.6%) and radioulnar synostosis was found in 2 (9.1%) cases. Conclusion: It was found that ulnar translocation in conjunction with wrist arthrodesis is an easy reconstructive technique that preserves function, produces outstanding results, and has few problems.